Analisis Minat Membuka Media Sosial Terhadap Konsentrasi Mahasiswa Menggunakan Metode Statistik Deskriptif - Kaisha az, Ratu; Aulia, Putri; Alfharizi, Ananda; Hafiz; Oktavia Nst, Adelyna (Papanda, 2025)
This study aims to determine the effect of interest in accessing social media on the concentration levels of Information Systems students from the 2023 cohort at the State Islamic University of North Sumatra. The research employed a quantitative method with a descriptive statistical approach and correlation analysis. Data were obtained from questionnaires voluntarily completed by 50 students. Each respondent provided a score for their interest in accessing social media (scale 1–5) and a daily concentration level score (scale 1–5). The collected data were processed using percentage analysis to observe the distribution of both variables, followed by correlation analysis. The results showed that most students fell into the moderate (30%) and high (20%) categories of social media interest. Meanwhile, concentration scores were predominantly in the moderate (22%) and high (20%) categories. A negative relationship trend was found between interest in accessing social media and concentration level; students who reported very high interest tended to have lower concentration levels, and vice versa. These findings are consistent with literature stating that social media is a major source of distraction that can reduce academic performance. Therefore, it can be concluded that high usage of social media has the potential to decrease students' concentration in daily activities.